Examples of folk oral creativity and their advantages and difficulties in the development of competency of intercultural communication of students. - Tajiboyeva Fotimaxon Voxidjon qizi (Periodica Journal, 2025)
This article examines the role of folk oral creativity in the development of intercultural communication competency among students. Various forms of oral folk traditions, such as proverbs, fairy tales, epics, and songs, are analyzed in relation to their contribution to fostering cross-cultural understanding. The study highlights both the advantages and challenges associated with integrating these elements into educational programs. The findings suggest that folk oral creativity enhances students' cultural awareness, language skills, and appreciation of diversity, while also presenting challenges such as contextual interpretation and linguistic barriers. The paper provides practical suggestions for overcoming these challenges and enhancing the effectiveness of oral folk traditions in education
Keywords: intercultural communication; student competency; folk oral creativity